The presentation of celiac disease in 220 Turkish children - Balamtekin, Necati; Uslu, Nuray; Baysoy, Gökhan; Usta, Yusuf; Demir, Hülya; Saltik-Temizel, Inci Nur; Ozen, Hasan; Gürakan, Figen; Yüce, Aysel (The Turkish Journal of Pediatrics, 2010)
The aim of this study was to investigate the presentation pattern of newly diagnosed celiac disease (CD) in Turkish children in the last eight years. Two hundred twenty patients with newly diagnosed CD were included. The medical records of all the patients between January 2000 and October 2008 were reviewed. The clinical spectrum was divided into three categories according to the main symptoms that led to the diagnosis: gastrointestinal presentation, non-gastrointestinal presentation, and silent cases. The mean age of the patients was 7.2 +/- 4.3 years at diagnosis. According to the presenting signs, the patients were defined as gastrointestinal presentation (129 patients, 58.6%), non-gastrointestinal presentation (76 patients, 34.6%) and silent cases (15 patients, 6.8%). This study showed that the number/percentage of CD cases who presented with non-gastrointestinal symptoms/conditions, so-called "non-gastrointestinal presentation", have been increasing in the last eight years.